1993
DOI: 10.1007/bf01318998
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of three non structural proteins of a porcine group C (Cowden strain) rotavirus

Abstract: Sequences of three gene products of a group C (Cowden strain) rotavirus are presented and compared with the sequences of the corresponding group A (SA11) proteins. The degree of similarity for gene 7, 9, and 10 is respectively 34%, 58%, and 45%. Comparison of these 2 viruses allowed to identify several regions well conserved. In the protein coded by Cowden segment 7 (NS 53) only a short cystein and histidine rich region, presenting the zinc finger consensus motif, is common to group A (segment 5) and group C s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…of 83 kD is equivalent to the vp 4 hemagglutinin of group A rotavirus. In contrast to previous studies [3,9,11], we identified a polypeptide with a mol. wt.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…of 83 kD is equivalent to the vp 4 hemagglutinin of group A rotavirus. In contrast to previous studies [3,9,11], we identified a polypeptide with a mol. wt.…”
Section: Discussioncontrasting
confidence: 84%
“…[11] reported that group C rotavirus incorporated 3 H-mannose into two proteins, suggesting that group C rotavirus also contains high mannose glycoproteins. We found that 3 Hmannose was also incorporated into two polypeptides and like Bremont et al [3] we found one of these polypeptides to be a structural glycoprotein. These findings are, however, in contrast to a previous study [1 I] reporting a 25 kD possible structural glycoprotein in addition to the vp 7 structural glycoprotein.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Comparison with the porcine strain showed sequence heterogeneity was distributed throughout the protein with average identity of only 87.4%. The predicted molecular weight of the larger open reading frame (38 kDa) for the Bristol VP7 was in general agreement with the molecular weight determined by sodium dodecyl sulfate (SDS)-PAGE for the porcine (Cowden) VP7 glycoprotein [Bremont et al, 1988; Jiang et al, 19901. Three potential N-linked glycosylation sites (Asn-X-Ser/Thr) were present within the human sequences (at residues 67, 152, and 225) but only two in the porcine sequence at residues 67 and 225.…”
mentioning
confidence: 70%